GEOGRAPHICAL INDICATIONS IN INDIA & THE CASE OF FAMOUS INDIAN WEAVE: BANARASI BROCADE - Gulati, Shruti (International Journal of Research -GRANTHAALAYAH, 2016)
A milestone was reached when WTO through TRIPS had granted goods to retain its essence of the land by allowing attaching a geographical indication to goods having specialty from the place of origin. Where a product holds characteristics that clearly indicate its reference to a place in terms of quality, essentially attributed things such as reputation, it is said to have a geographical indication. Where most things become synonymous with the land, that they sometimes lose their own identity leading to an interchangeable use of the geographical name with the good like the ‘banarasibrocade’or ‘phulkari’. The reason for getting it under the Intellectual Property Right radar is that it becomes the selling point as well as that characteristic which solely differentiates the good out of the crowd, sometimes to an extent of premium pricing as well. It’s like a safeguard to both the consumers for an assurance of quality and the producers for making it worthy.